Self-assessment Q & A in clinical laboratory science. - Wu, Alan H. B. (Elsevier, 2021)
Self-assessment Q & A in Clinical Laboratory Science, III, adds a variety of subject matter that addresses new concepts and emerging technology, particularly in the areas of kidney biomarkers, cancer biomarkers, molecular diagnostics, multiple myeloma, pharmacogenomics, novel cardiovascular biomarkers and biomarkers of neurologic diseases. The field of Clinical Laboratory Science continues to evolve and editor Alan Wu has once again brought together experts in the field to cover the contemporary topics that are being tested today. This updated bank of questions and answers is a must-have to sharpen knowledge and skills. Contains nearly 800 multiple choice questions with correct answer explanations Assists readers in determining knowledge gaps so they can better study for certification examinations and remain current in this rapidly changing field Provides a format that is conducive to quick learning in digestible segments Includes beneficial citations for additional study.